Moss endemism in the Mexican flora. Issue 5 (4th July 2019) - Delgadillo-Moya, Claudio; Peña-Retes, Ana Paola; Villaseñor, José Luis; Ortiz, Enrique
Abstract : Although the moss flora of Mexico consists of nearly 1000 species, only 77 are endemic. The country has many poorly collected or unexplored areas, but the number of endemic mosses is not expected to undergo a substantial increase; percent endemism has in fact decreased with taxonomic revisions and monographs and better exploration in other countries. Literature and herbarium records ( n  = 584) were used to obtain an updated list of endemic mosses and their state distribution in Mexico. Cluster analysis and mapping indicate that there are three main areas of endemism: Lowland areas in various states, the mountain area along 19–20°N lat., and the highlands in Oaxaca and Chiapas. Similarity by province shows that Trans-Mexican Volcanic Belt, Sierra Madre Oriental, Chihuahuan Desert, and Sierra Madre del Sur have the highest numbers of endemic species. Five monotypic genera and 76 species (including two infraspecific taxa), many of which have comparatively narrow geographical ranges, suggest that speciation is recent, that species have had little time to disperse, and were formed by Pleistocene environmental climates in the highlands; older speciation may be represented by widespread disjunct species that still are found in the highlands of Mexico.